The classification and differential diagnosis of absence seizures with short-term video-EEG monitoring during childhood - Uysal-Soyer, Özge; Yalnızoğlu, Dilek; Turanlı, Güzide (The Turkish Journal of Pediatrics, 2012)
Absence seizures are idiopathic epilepsies characterized by impairment of consciousness and generalized 2.5-4 Hz spike and slow wave discharges. This prospective study was performed to classify and define properties of subgroups of absence epilepsies. We included 31 patients, of whom seven were in the differential diagnosis group. On admission, absence epilepsy provisional diagnosis was considered in 16 patients clinically and in the other 15 patients based on routine EEG findings. Ictal EEGs were recorded by video-EEG monitoring in 23 of the patients (totally 202 ictal recordings). Patients were diagnosed as childhood absence epilepsy (n=8), juvenile absence epilepsy (n=10), juvenile myoclonic epilepsy (n=3), eyelid myoclonia with absences (n=2), and perioral myoclonia with absences (n=1). Neuroimaging, video-EEG monitoring and especially ictal recordings are important for classification of epilepsies in addition to history, physical examination and routine EEG findings. Video-EEG monitoring is required to classify, to make differential diagnosis and to determine the treatment plan and prognosis.